Psoas muscle fluorine‐18‐labelled fluoro‐2‐deoxy‐d‐glucose uptake associated with the incidence of existing and incipient metabolic derangement. Issue 4 (15th May 2019) - Kim, Ji Young; Jun, Dae Won; Choi, Jun; Nam, Eunwoo; Son, Donghee; Choi, Yun Young
Abstract: Background: Skeletal muscle glucose utilization is an important component of whole‐body glucose consumption in normal humans. Fluorine‐18‐labelled fluoro‐2‐deoxy‐d‐glucose ( 18 F‐FDG) is a non‐invasive molecular imaging probe for evaluating tissue glucose utilization. It remains unclear whether or not 18 F‐FDG uptake by skeletal muscle has utility as a biomarker for metabolic derangement. We investigated the utility of measurement of muscle 18 F‐FDG positron emission tomography/computed tomography uptake as a surrogate marker for existing and incipient metabolic abnormalities. Methods: Fluorine‐18‐labelled fluoro‐2‐deoxy‐d‐glucose ( 18 F‐FDG) uptakes of insulin‐sensitive organs (liver, pancreas, mesenteric visceral fat, psoas muscle, and abdominal subcutaneous fat) and their association with metabolic abnormalities were evaluated in an experimental group comprising 91 men and 66 women (mean age 49.9 ± 11.1 years). In this cross‐sectional cohort, we assessed the predictive power of the optimal cut‐off 18 F‐FDG uptake [maximum standardized uptake value (SUVmax )]. We confirmed its feasibility and reliability for diagnosis of existing and incipient metabolic derangement in the validation group (longitudinal cohort comprising 91 men and 67 women; mean age 52.6 ± 7.9 years). Results: Fluorine‐18‐labelled fluoro‐2‐deoxy‐d‐glucose ( 18 F‐FDG) uptake (SUVmax ) of psoas muscle was strongly correlated with clinical metabolic parameters in the experimental group. It was positively correlated with waist circumference, body mass index, fasting glucose, triglyceride, systolic and diastolic pressure, and negatively correlated with high‐density lipoprotein cholesterol levels (for all, P < 0.05). SUVmax of the psoas muscle also showed the best area under the curve value (0.779) as a predictor of metabolic syndrome (MetS) in the experimental group. Using the optimal cut‐off SUVmax of 1.34, the sensitivity, specificity, accuracy, positive, and negative predictive value for predicting existing MetS in the experimental group were 70.0%, 84.6%, 80.9%, 60.9%, and 89.2%, respectively. In the validation group, corresponding values were 47.6%, 92.3%, 86.1%, 50.0%, and 91.6%, respectively. Existing and incipient MetS were significantly higher in subjects with high 18 F‐FDG uptake by the psoas muscle (SUVmax > 1.34). Subjects with higher psoas muscle SUVmax had a 3.3‐fold increased risk of developing MetS ( P = 0.017). Conclusions: Fluorine‐18‐labelled fluoro‐2‐deoxy‐d‐glucose ( 18 F‐FDG) uptake of psoas muscle is a promising surrogate marker for existing and incipient metabolic derangement.